Testing And Assessment In English Language Instruction - Farida Hanim Saragih (BAHAS, 2016)
This present paper aims at discussing the term Testing and Assessment and also the use of them in English language instruction. Most of the teachers consider both testing and assessment are the same aspects; assessment is much more than test. Assessment refers to a variety of ways collecting information on learners’ language ability or achievement, although testing and assessment are often used interchangeably, assessment is an umbrella term for all types of measures used to evaluate students’ progress and test is a subcategory of assessment. Teachers are used to on their own in constructing tests to measure students’ progress and performance. The result is they write traditional grammar-based items in a discrete point format that doesn’t fit the communicative of the learning materials or the underlying teaching principles. By having a better understanding both testing and assessment, teachers can distinguish and  identify both of them and it is hoped that they can create or construct better testing and assessment for their students based on teaching principles.  Keywords: Testing, Assessment